2015
DOI: 10.29074/ascls.28.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Blood Ammonia Stability Revisited

Abstract: The instability of ammonia in whole blood has challenged clinical laboratory scientists to develop specimen collection and handling methods that produce reliable results for plasma ammonia concentration. Thirty-eight outpatients' plasma ammonia concentrations were measured after heparinized whole blood specimens from each subject were held for 5, 15, and 30 minutes at room temperature and "on-ice". The plasma ammonia concentration from whole blood maintained "on-ice" for 5 minutes was designated the "reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…This deamidation reaction also releases ammonia, contributing to an increase in ammonia concentrations with increasing storage time. Ammonia was significantly increased after 72 h of storage at 4 °C and this finding is consistent with results from previous studies [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This deamidation reaction also releases ammonia, contributing to an increase in ammonia concentrations with increasing storage time. Ammonia was significantly increased after 72 h of storage at 4 °C and this finding is consistent with results from previous studies [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Another limitation of our study is the small sample size used for the short-term stability testing. While the results of this portion of the study may be considered preliminary, they do correspond well to what has been shown in the literature in regard to amino acid stability [ 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, the estimation of clearance is problematic because ammonia is an unstable molecule [41, 42] and its levels are affected by sample temperature [30]. This requires specimen collection, handling, and transport on ice.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in ammonia in whole blood are greater than those in plasma, with greater increases at higher temperatures. [14][15][16][17][18][19][20] In a study where blood was collected from healthy volunteers (n = 36), whole blood ammonia concentrations increased by 3.9 μmol/L per hour at 0°C, 5.2 μmol/L at 20°C and 25.2 μmol/L per hour at 37°C from a mean ammonia concentration of 23.0 μmol/L. In plasma ammonia concentrations increased by 0.4 μmol/L per hour at 0°C, 1.4 μmol/L per hour at 20°C and 4.2 μmol/L per hour at 37°C from a mean ammonia concentration of 23.0 μmol/ L. 14 Therefore, speedy delivery of the sample to the laboratory and rapid analysis is required to minimise such increases.…”
Section: Sample Rejectionmentioning
confidence: 99%
“…Pre-analytical factors, such as haemolysis, delayed sample separation and inappropriate sample storage, can lead to artificially high results. [13][14][15][16][17][18][19][20] Laboratories have an important role in optimising pre-analytical processes, for example, by providing clear guidance on sample collection and handling so that pre-analytical errors can be minimised. Quality goals and sample acceptance criteria need to reflect the clinical utility of the test.…”
Section: Introductionmentioning
confidence: 99%